Volume Measurement System of Used Cooking Oil (UCO) Using Internet of Things and Web-Based System - Koto, Zulafrilian; Anandika, Arrya; Sato, Yuta; Pramawahyudi, Pramawahyudi; Syahputra, Ronaldo (Universitas Andalas, 2026)
One of the main issues is the discrepancy between the measured and actual oil volumes of used cooking oil (UCO). Using a measurement tank as the measuring medium and an ultrasonic sensor as the tool, a system was developed to automatically measure oil volume with high accuracy. This system allows users to continuously measure oil volume using a servo motor that directs the oil into a storage tank. The system is designed to notify the company and customers via an LCD display and website when the oil measurement is completed. The system successfully measures oil volume using the ultrasonic sensor, achieving an accuracy of 96.74% during implementation.